Protective role of VEGF/VEGFR2 signaling against high fatality associated with hepatic encephalopathy via sustaining mitochondrial bioenergetics functions - Tsai, Ching-Yi; Wu, Jacqueline C. C.; Wu, Chiung-Ju; Chan, Samuel H. H. (Journal of biomedical science, 2022)
Background The lack of better understanding of the pathophysiology and cellular mechanisms associated with high mortality seen in hepatic encephalopathy (HE), a neurological complication arising from acute hepatic failure, remains a challenging medical issue. Clinical reports showed that the degree of baroreflex dysregulation is related to the severity of HE. Furthermore, mitochondrial dysfunction in the rostral ventrolateral medulla (RVLM), a key component of the baroreflex loop that maintains blood pressure and sympathetic vasomotor tone, is known to underpin impairment of baroreflex. Realizing that in addition to angiogenic and vasculogenic effects, by acting on its key receptor (VEGFR2), vascular endothelial growth factor (VEGF) elicits neuroprotection via maintenance of mitochondrial function, the guiding hypothesis of the present study is that the VEGF/VEGFR2 signaling plays a protective role against mitochondrial dysfunction in the RVLM to ameliorate baroreflex dysregulation that underpins the high fatality associated with HE. Methods Physiological, pharmacological and biochemical investigations were carried out in proof-of-concept experiments using an in vitro model of HE that involved incubation of cultured mouse hippocampal neurons with ammonium chloride. This was followed by corroboratory experiments employing a mouse model of HE, in which adult male C57BL/6 mice and VEGFR2 wild-type and heterozygous mice received an intraperitoneal injection of azoxymethane, a toxin used to induce acute hepatic failure. Results We demonstrated that VEGFR2 is present in cultured neurons, and observed that whereas recombinant VEGF protein maintained cell viability, gene-knockdown of vegfr2 enhanced the reduction of cell viability in our in vitro model of HE. In our in vivo model of HE, we found that VEGFR2 heterozygous mice exhibited shorter survival rate and time when compared to wild-type mice. In C57BL/6 mice, there was a progressive reduction in VEGFR2 mRNA and protein expression, mitochondrial membrane potential and ATP levels, alongside augmentation of apoptotic cell death in the RVLM, accompanied by a decrease in baroreflex-mediated sympathetic vasomotor tone and hypotension. Immunoneutralization of VEGF exacerbated all those biochemical and physiological events. Conclusions Our results suggest that, acting via VEGFR2, the endogenous VEGF plays a protective role against high fatality associated with HE by amelioration of the dysregulated baroreflex-mediated sympathetic vasomotor tone through sustaining mitochondrial bioenergetics functions and eliciting antiapoptotic action in the RVLM. Keywords: Acute liver failure, Primary neuronal culture, Mitochondrial membrane potential, Bioenergetics failure, Apoptosis, Baroreflex dysregulation